CHRISTINA ZAMON, The Lone Arranger: Succeeding in a Small Repository - Wilkinson, Sarah (Archivaria, 2012)
The Lone Arranger: Succeeding in a Small Repository. CHRISTINA ZAMON. Chicago: Society of American Archivists, 2012. vi, 157 p. ISBN 1-931666-41-5.